Importance of Family Connection for Healthy Weight Behaviors Amid Adverse Family Experiences and Behavioral Difficulties. Issue 9 (December 2021) - Hayes, Katey; Davis, Angelia; Zlomke, Kimberly; Fruh, Sharon
ABSTRACT: Objective: Adverse family experiences (AFEs), including parent divorce and domestic violence, negatively affect obesogenic behaviors and engagement in healthy weight behaviors (HWBs). The current study used a moderated mediation model to investigate the role of family connection in the relationship between AFEs and HWBs for children with behavioral difficulties. Method: Youth (6–17 years old; n = 13, 921) from the 2016 National Survey of Children's Health data set were included in the study. Results: Family connection mediated the relationship between AFEs and each HWB. The models of physical activity and screen time had significant direct effects. Behavioral difficulties moderated the direct effect of AFEs and screen time and physical activity. Conclusion: Family connection mediated the relationships between each HWB and AFEs. The findings suggest that for children without behavioral difficulties, family connection was a stronger protective factor for adequate physical activity and decreased screen time.